GOOD PRACTICES OF TEACHERS IN LEARNING SCIENCES IN PRIMARY SCHOOLS - Lasmawan, I Wayan; Kertih, I Wayan; Anggreni, Ni Luh Putu Yesy; Astuti, Ni Wayan Widi; Cahayani, Ni Luh Putu; Liska, Luh De (Indonesian Journal of Educational Development (IJED), 2023)
Social studies education as a field of study given at the educational level in the school environment, not only provides knowledge, but also provides values, attitudes and skills in the lives of students in society, nation and state in various characteristics. To make social studies learning enjoyable for students, there needs to be teacher innovation and creativity in delivering learning in class. Because even now, social studies still seems to be neglected and is considered rote. Through the application of virtual classroom learning media with the help of e-modules and learning videos in social studies learning for class VI students at SD Negeri 7 Sesetan, it can have a positive impact on students. In accordance with data collection carried out by distributing questionnaires to 31 students in class VI of SD Negeri 7 Sesetan, the results obtained were that 95% of students gave positive responses and enjoyed participating in the learning carried out by the teacher.